Comparing regional stove‐usage patterns and using those patterns to model indoor air quality impacts. (24th February 2020) - Piedrahita, Ricardo; Johnson, Michael; Bilsback, Kelsey R.; L'Orange, Christian; Kodros, John K.; Eilenberg, Sarah Rose; Naluwagga, Agnes; Shan, Ming; Sambandam, Sankar; Clark, Maggie; Pierce, Jeffrey R.; Balakrishnan, Kalpana; et al.
Abstract: Monitoring improved cookstove adoption and usage in developing countries can help anticipate potential health and environmental benefits that may result from household energy interventions. This study explores stove‐usage monitor (SUM)‐derived usage data from field studies in China (52 stoves, 1422 monitoring days), Honduras (270 stoves, 630 monitoring days), India (19 stoves, 565 monitoring days), and Uganda (38 stoves, 1007 monitoring days). Traditional stove usage was found to be generally similar among four seemingly disparate countries in terms of cooking habits, with average usage of between 171 and 257 minutes per day for the most‐used stoves. In Honduras, where survey‐based usage data were also collected, there was only modest agreement between sensor data and self‐reported user data. For Indian homes, we combined stove‐usage data with a single‐zone Monte Carlo box model to estimate kitchen‐level PM2.5 and CO concentrations under various scenarios of cleaner cookstove adoption. We defined clean cookstove performance based on the International Standards Organization (ISO) voluntary guidelines. Model results showed that even with 75% displacement of traditional stoves with the cleanest available stove (ISO tier‐5), World Health Organization 24 hours PM2.5 standards were exceeded in 96.4% of model runs, underscoring the importance of full displacement.